Analisis Pengeringan Kacang Panjang (Vigna unguiculata): Perbandingan Metode Pengeringan Sinar Matahari dan Pengeringan Beku - Azis, Yusuf Ma'rifat Fajar; Ilmi, Nurika Nazilatul; Sulistyo, Khansa Praningdita; Kamilia, Salsa; Satya Mukti, I Gusti Ngurah (Program Studi Teknologi Pangan, 2025)
Long beans (Vigna unguiculata) are a highly nutritious vegetable that are susceptible to spoilage due to their high moisture content. This study aims to investigate the drying efficiency of long beans using two methods: sun drying and freeze drying. The primary objective is to compare the reduction in mass of the product achieved by each method, thereby determining the most effective drying technique. Moisture content, material mass, and drying rate were measured from the beginning to the end of the drying process at 12-hour intervals over a period of 7 days. The results showed that sun drying effectively reduced moisture content more quickly by utilizing natural heat, while freeze drying provided more consistent temperature control. Although the drying rate was slower, the freeze drying method preserved color and texture better compared to sun drying. Statistical analysis using ANOVA revealed that the differences in drying methods significantly affected mass reduction (p 0.05). The findings of this study are expected to provide practical insights for small-scale farmers and food processors in selecting the appropriate drying method for long beans based on resource availability and desired product characteristics.